Practical Approach to Problem-Solving Movement Tasks Limited by an Ankle Dorsiflexion Restriction. Issue 6 (December 2017) - Howe, Louis; Waldron, Mark; North, Jamie
Abstract : ABSTRACT: LIMITATIONS IN ANKLE DORSIFLEXION RANGE OF MOTION HAVE BEEN SHOWN TO INCREASE COMPENSATORY MOVEMENTS AT BOTH PROXIMAL AND DISTAL JOINT SEGMENTS IN THE LOWER EXTREMITY. THIS ARTICLE DISCUSSES METHODS TO ASSESS AND CORRECT DEFICIENCIES IN ANKLE DORSIFLEXION RANGE OF MOTION. PREVIOUSLY, HOWEVER, THE REMOVAL OF JOINT RESTRICTIONS HAS NOT BEEN SHOWN TO REDUCE COMPENSATORY STRATEGIES DEVELOPED THROUGH SUCH RESTRICTIONS. THEREFORE, THIS ARTICLE WILL ALSO DISCUSS IMPORTANT CONSIDERATIONS FOR FACILITATING THE RELEARNING PROCESS AND PROPOSE KEY PRINCIPLES FOR DEVELOPING A CORRECTIVE PROGRAM.